Development of a digital-propeller- anemometer / Abdul Rahim Mahamad Sahab, Mohd. Kamel Wan Ibrahim and Nor Hayati Saad - Mahamad Sahab, Abdul Rahim; Wan Ibrahim, Mohd. Kamel; Saad, Nor Hayati (1999)
The science of instrumentation is of fundamental importance to engineers, scientist, and medical workers. Instruments are the eyes and ears of the technologists. Without sensors and their associated signal processing systems there would be no modern instrument. The progress that has been made in almost all areas of technology can be seen in terms of the rate at which the necessary instrumentation has been developed. For example in recent years many improvements have been made to the performance of the internal combustion engine. One of the reasons is that in the last few years sensor have been developed which allow investigations to be made of the ways in which the flame front spreads inside the cylinder after ignition. The process of instrumentation is often considered solely in terms of the sensors used and their associated electronics. However, there are two step involved in making any measurement. These are, first, getting the data, which is where sensors and electronics are used and second, analyzing it.